A Trust Model for Electrical Stove Technology Acceptance of Indonesian Stereotype - Fajri, Nofias; Baharuddin, Andi Velahyati; Putera, Dimas Akmarul; Faujiyah, Firdhani (Jurnal Sistem Teknik Industri, 2024)
The surge in LPG consumption within Indonesian households, coupled with stagnant LPG production, has compelled the government to import 75% of LPG by 2022. Despite initial plans for a transition to electric stoves in 2023, the program was halted due to widespread public resistance to electric stove technology. The rejection was attributed, in part, to low trust in this emerging technology, emphasizing the pivotal role of trust in influencing technological acceptance. In response, this research endeavors to construct a robust and reliable model capturing trust in the acceptance of electric stove technology. Utilizing the PLS Structural Equation Model method for data analysis, the focus centers on two trust indicators: propensity trust and human-machine trust. In the quest for a valid model, the statistical modeling technique considers five initial hypotheses developed with 32 trust-related items. Upon analysis, one hypothesis is rejected, while four are accepted. Notably, the trust human-machine (THM) variable emerges as a significant influencer of trust for electric stove technology (TTK), substantiated by a path coefficient of 0.917 and p = <0.001. Thus, the resulting model takes on a reflective form, offering insights into the intricate dynamics of trust in the acceptance of electric stove technology.